Molecular genetic analysis of phosphatase and tensin homolog and p16 tumor suppressor genes in patients with malignant glioma - Abdullah, Jafri Malin; Zainuddin, Norafiza; Sulong, Sarina; Isa, Mohd. Nizam; Jaafar, Hasnan (Journal of Neurosurgery Publishing Group, 2003)
Object. Several genes have been shown to carry mutations in human malignant gliomas, including the phosphatase and tensin homolog (PTEN) deleted on chromosome 10 and p16 tumor suppressor genes. Alterations of this gene located on chromosome 10 q23 and 9p21, respectively, may contribute to gliomagenesis. In this study, the authors analyzed 20 cases of malignant gliomas obtained in patients living on the east coast of Malaysia to investigate the possibilities of involvement of the PTEN and p16 genes. Methods. Samples of DNA were amplified by polymerase chain reaction (PCR), analyzed by single-stranded conformation polymorphism (SSCP), and subsequently by sequencing. Two cases of glioblastoma multiforme, three cases of anaplastic astrocytoma, one case of anaplastic pleomorphic xanthoastrocytoma, and one case of anaplastic ependymoma showed SSCP band shifts in PTEN mutational analyses. The DNA sequencing analyses of these samples revealed missense and nonsense mutations, with cluster of mutations in the region 5 to the core phosphatase motif of exon 5 and the 5-end of exon 6. No abnormal migration shifts were detected in the glioma samples analyzed for point mutations of the p16 gene. Homozygous deletions of p16 were also not detected in all samples. Conclusions. These findings indicate that mutations of the PTEN genes were likely to contribute to the tumorigenesis and morphological transformations of gliomas. In addition, the alterations of the p16 gene might not play a major role in tumorigenesis of malignant gliomas in Malaysian patients.